Nitrogen-sulfur double-doped layered manganese dioxide material as well as preparation method and application thereof

By using nitrogen-sulfur double-doped layered manganese dioxide material as the positive electrode material in zinc-manganese batteries, the problems of poor electronic conductivity and structural instability of manganese-based positive electrode materials in zinc-manganese batteries are solved, and higher electrochemistry is achieved Performance and cycle stability.

CN119461490APending Publication Date: 2025-02-18BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411645529.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Manganese-based positive electrode materials have problems such as poor electronic conductivity, insufficient ion diffusion path, structural instability and low capacity in zinc-manganese batteries, resulting in poor rate performance and cycle life.

Method used

By doping thiourea and manganese dioxide in a dual-temperature tube furnace, nitrogen and sulfur elements are introduced to form a nitrogen and sulfur double-doped layered manganese dioxide material, and the electronic structure and structural stability of the material are adjusted.

Benefits of technology

It improves the intrinsic conductivity and structural stability of manganese dioxide materials, enhances the reversible capacity and overall capacity of the material, and improves the rate performance and cycle life of zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461490A_ABST
    Figure CN119461490A_ABST
Patent Text Reader

Abstract

The invention provides a nitrogen-sulfur double-doped layered manganese dioxide material as well as a preparation method and application thereof, and relates to an electrochemical energy storage material. Thiourea is placed in a first temperature area, manganese dioxide is placed in a second temperature area (150-200 DEG C), the thiourea is decomposed into hydrogen sulfide and ammonia gas in the first temperature area, the hydrogen sulfide and the ammonia gas are carried by carrier gas to be conveyed into the second temperature area to be subjected to doping reaction with the manganese dioxide, and the nitrogen-sulfur double-doped layered manganese dioxide material is obtained. The manganese dioxide is delta-phase layered manganese dioxide. Nitrogen and sulfur elements are doped into manganese dioxide through a low-temperature roasting method, the intrinsic conductivity and structural stability of manganese dioxide are improved, the material has high reversible capacity, and the formation of part of oxygen vacancies can help the material expose active sites, so that the overall capacity of the material is improved. The nitrogen-sulfur double-doped layered manganese dioxide material is used as a positive electrode material for a zinc ion battery, and has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to electrochemical energy storage materials, and in particular to a nitrogen-sulfur dual-doped layered manganese dioxide material and a preparation method and application thereof. Background Art

[0002] Secondary batteries generally have high energy density and occupy a major part in electrical energy storage systems (EES). Among the secondary battery systems, aqueous zinc-ion batteries have attracted much attention due to their low cost, high safety and high cycle performance. Aqueous zinc-ion batteries use zinc as the negative electrode, and the positive electrode materials are mainly divided into organic materials and inorganic materials. Compared with other secondary batteries, zinc-ion batteries have the characteristics of high energy density, low cost, and abundant content in the earth's crust. The reaction mechanism of aqueous zinc-ion batteries is similar to the energy storage mechanism of lithium-ion batteries. The redox process is completed based on the embedding / ex-embedding behavior of ions inside the electrode material. Compared with commercial lithium-ion batteries, zinc-ion batteries can be assembled in the air, thereby reducing the cost of the battery, enabling high current charging, and greatly shortening the charging time. Compared with lithium, zinc can exist stably in the air. At the same time, water as an electrolyte solvent greatly improves the safety of the battery. Thanks to the high stability of zinc at room temperature and the ability to deposit it on flexible conductive materials using electrochemical deposition methods, aqueous zinc-ion batteries will be able to be made into flexible batteries to provide energy for flexible devices.

[0003] As an intrinsically safe energy storage system, the new zinc-ion battery has great application prospects in the field of large-scale energy storage and the development and utilization of clean energy. Among them, aqueous zinc-manganese batteries have become the energy storage technology with the greatest commercial potential due to their high theoretical capacity and low cost. However, there are still many scientific challenges in the practical application of manganese-based positive electrode materials: (1) Manganese-based positive electrode materials have poor intrinsic electronic conductivity and insufficient ion diffusion paths, resulting in poor rate performance of the battery; (2) Manganese-based positive electrode materials are prone to structural instability, irreversible structural phase change, dissolution and other problems during the cycle process, resulting in a short battery cycle life; (3) There are few energy storage active sites in the positive electrode material structure, which reduces the overall capacity of the battery. The above problems limit the further large-scale development of zinc-manganese batteries. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a nitrogen-sulfur dual-doped layered manganese dioxide material and a preparation method and application thereof. The nitrogen-sulfur dual-doped layered manganese dioxide material prepared by the present invention has excellent electrochemical properties as a positive electrode material for zinc ion batteries.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a nitrogen-sulfur dual-doped layered manganese dioxide material, comprising the following steps:

[0007] The thiourea is placed in a first temperature zone, and the manganese dioxide is placed in a second temperature zone. The thiourea is decomposed into hydrogen sulfide and ammonia in the first temperature zone. The hydrogen sulfide and ammonia are transported to the second temperature zone under the carrier gas to react with the manganese dioxide to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material; the manganese dioxide is a δ-phase layered manganese dioxide, and the temperature of the second temperature zone is 150-200°C.

[0008] Preferably, the mass ratio of manganese dioxide to thiourea is 1:(0.15-0.3).

[0009] Preferably, the mass ratio of manganese dioxide to thiourea is 1:0.2.

[0010] Preferably, the temperature of the first temperature zone is 220-300°C.

[0011] Preferably, the temperature of the second temperature zone is 170-180°C.

[0012] Preferably, the carrier gas is argon, and the flow rate of the carrier gas is 20 to 50 mL / min.

[0013] Preferably, the doping reaction time is 10 to 60 minutes.

[0014] The present invention provides a nitrogen-sulfur dual-doped layered manganese dioxide material prepared by the preparation method described in the above technical solution, comprising a delta-phase layered manganese dioxide and nitrogen and sulfur elements doped in the delta-phase layered manganese dioxide.

[0015] The present invention provides a zinc ion battery, wherein the positive electrode material of the zinc ion battery comprises the nitrogen-sulfur dual-doped layered manganese dioxide material described in the above technical solution.

[0016] Preferably, the electrolyte of the zinc ion battery comprises ZnSO4, MnSO4 and water.

[0017] The present invention provides a preparation method of a nitrogen-sulfur doped layered manganese dioxide material, comprising the following steps: placing thiourea in a first temperature region, placing manganese dioxide in a second temperature region, the thiourea being decomposed into hydrogen sulfide and ammonia in the first temperature region, the hydrogen sulfide and ammonia being carried by a carrier gas to the second temperature region for doping reaction with manganese dioxide to obtain a nitrogen-sulfur doped layered manganese dioxide material; the manganese dioxide is a δ-phase layered manganese dioxide, and the temperature of the second temperature region is 150-200°C. The present invention performs nitrogen-sulfur doping on manganese dioxide, and uses the introduced heteroanionic nitrogen and sulfur elements to adjust the electronic structure of the material, thereby improving the intrinsic conductivity of the manganese dioxide material; the bond energy of the Mn-N bond is higher and more stable, which can improve the structural stability of the manganese dioxide material and make the material have a high reversible capacity; the introduction of anionic nitrogen and sulfur elements realizes the formation of partial oxygen vacancies, helps the material expose active sites, and thus improves the overall capacity of the material. In addition, the method of the present invention has a relatively low temperature and adopts a low-temperature roasting method to dope nitrogen and sulfur elements into manganese dioxide, thereby ensuring that the nitrogen and sulfur elements are uniformly introduced into the manganese dioxide lattice while retaining the original layered structure of manganese dioxide.

[0018] The present invention provides a nitrogen-sulfur dual-doped layered manganese dioxide material prepared by the preparation method described in the above technical solution. The nitrogen-sulfur dual-doped layered manganese dioxide material provided by the present invention has excellent electrochemical properties when used as a positive electrode material for zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD patterns of manganese dioxide (MnO2) before doping and nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0020] Figure 2 This is a scanning electron microscope image of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 1;

[0021] Figure 3 This is a transmission electron microscope image of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 1;

[0022] Figure 4 N1s photoelectron spectrum of manganese dioxide (MnO2) before doping and nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0023] Figure 5 The S2p photoelectron spectrum of manganese dioxide (MnO2) before doping and the nitrogen-sulfur co-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0024] Figure 6The Raman spectra of manganese dioxide (MnO2) before doping and the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0025] Figure 7 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0026] Figure 8 The charge-discharge curve of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0027] Fig. 9 The rate performance of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0028] Fig.10 The high current (1 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1;

[0029] Fig.11 The small current (0.2A / g) cycling performance of original manganese dioxide (MnO2);

[0030] Fig.12 is the charge and discharge curve of original manganese dioxide (MnO2);

[0031] Fig.13 The high current (1A / g) cycling performance of the original manganese dioxide (MnO2);

[0032] Fig.14 is the rate performance of original manganese dioxide (MnO2);

[0033] Fig.15 The low current (0.2 A / g) cycle performance of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1;

[0034] Fig.16 This is a high current (1 A / g) cycle diagram of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1;

[0035] Fig.17 The rate performance of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1;

[0036] Fig.18 CV cycle diagram of sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1;

[0037] Fig.19The low current (0.2A / g) cycling performance of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2;

[0038] Fig. 20 The high current (1A / g) cycling performance of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2;

[0039] Fig.21 CV cycle diagram of nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2;

[0040] Fig. 22 The rate performance of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2;

[0041] Fig.23 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 2;

[0042] Fig.24 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 3;

[0043] Fig.25 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 3;

[0044] Fig.26 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 4;

[0045] Fig. 27 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 5;

[0046] Fig.28 This is the small current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 4. DETAILED DESCRIPTION

[0047] The present invention provides a method for preparing a nitrogen-sulfur dual-doped layered manganese dioxide material, comprising the following steps:

[0048] The thiourea is placed in a first temperature zone, and the manganese dioxide is placed in a second temperature zone. The thiourea is decomposed into hydrogen sulfide and ammonia in the first temperature zone. The hydrogen sulfide and ammonia are transported to the second temperature zone under the carrier gas to react with the manganese dioxide to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material; the manganese dioxide is a δ-phase layered manganese dioxide, and the temperature of the second temperature zone is 150-200°C.

[0049] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0050] In the present invention, the manganese dioxide is a δ-phase layered manganese dioxide; the present invention has no special requirements on the source of the δ-phase layered manganese dioxide, and it is prepared by using commercially available products or by a preparation method well known to those skilled in the art. In an embodiment of the present invention, the δ-phase layered manganese dioxide is obtained by mixing potassium permanganate with water and subjecting the obtained potassium permanganate solution to a hydrothermal reaction; the concentration of the potassium permanganate solution is preferably 6 g / L, the temperature of the hydrothermal reaction is preferably 180°C, and the time is preferably 4 hours.

[0051] In the present invention, the mass ratio of manganese dioxide to thiourea is preferably 1:(0.15-0.3), which can be 1:0.15, 1:0.2, 1:0.25, 1:0.3, and preferably 1:0.2. In the present invention, when the mass ratio of manganese dioxide to thiourea is too small, the proportion of doping elements is too high, which will reduce the electrochemical capacity of the material; when the mass ratio of manganese dioxide to thiourea is too large, due to the small proportion of introduced doping elements, the improvement of its cycle stability and intrinsic conductivity is weak, and it cannot play a role in stabilizing the material structure.

[0052] In the present invention, the temperature of the first temperature zone is preferably 220-300°C, and can be 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, and is preferably 250°C. The thiourea decomposes into hydrogen sulfide and ammonia in the first temperature zone.

[0053] In the present invention, the temperature of the second temperature region is 150-200° C., and may be 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., and preferably 170-180° C. In the present invention, when the temperature of the second temperature region is too high, the original layered structure of manganese dioxide may be destroyed, resulting in a decrease in electrochemical performance; when the temperature of the second temperature region is too low, nitrogen and sulfur elements cannot effectively react with manganese dioxide to uniformly dope, resulting in a decrease in its electrochemical stability.

[0054] In the present invention, the carrier gas is preferably argon, and the flow rate of the carrier gas is preferably 20 to 50 mL / min, more preferably 25 to 35 mL / min.

[0055] In the present invention, the time of the doping reaction is preferably 10 to 60 minutes, more preferably 10 to 30 minutes. In the present invention, when the time of the doping reaction is too long, the nitrogen and sulfur doping ratio is high, and the heating time is too long, which may cause the structural change of the material, resulting in a decrease in its electrochemical capacity; when the time of the doping reaction is too short, thiourea may not be completely decomposed, resulting in a too low ratio of doping elements, which cannot stabilize the material structure and improve its conductivity, resulting in a decrease in its electrochemical performance.

[0056] In an embodiment of the present invention, the doping reaction is preferably carried out in a dual-zone tubular furnace. The present invention has no special requirements for the dual-zone tubular furnace, and a dual-zone tubular furnace familiar to those skilled in the art can be used. In the present invention, the first temperature zone and the second temperature zone are respectively the air inlet end (i.e., the air inlet side) and the air outlet end (i.e., the air outlet side) of the dual-zone tubular furnace, and the carrier gas is continuously introduced into the dual-zone tubular furnace from the air inlet end. In the dual-zone tubular furnace, the heating rate from room temperature to the target temperature of the second temperature zone is preferably 5°C / min, and the heating rate from room temperature to the target temperature of the first temperature zone is based on the simultaneous heating to the target temperature with the second temperature zone. In the dual-zone tubular furnace, the insulation time of the first temperature zone and the second temperature zone is the time of the doping reaction. During the insulation process, thiourea decomposes into hydrogen sulfide and ammonia, which are transported to the air outlet end, and react with manganese dioxide at the air outlet end to obtain manganese dioxide doped with nitrogen and sulfur elements.

[0057] In the present invention, after the doping reaction is completed, the reaction mixture is cooled to room temperature; the cooling is performed under a protective atmosphere, and the protective atmosphere is preferably argon. In an embodiment of the present invention, the cooling is preferably natural cooling with the furnace.

[0058] Existing element doping usually adopts high temperature method. For example, in integrated circuit manufacturing, the doping temperature is usually 950-1280℃, which is to activate impurities and optimize electrical properties; in the doping of negative electrode materials of lithium batteries, such as SiO / graphite composite negative electrode, the doping temperature may need to be higher to achieve better deintercalation kinetics. The present invention uses low-temperature roasting method to modify manganese dioxide by nitrogen and sulfur doping. The process is simple and the reaction temperature is low. While ensuring that the original layered structure of manganese dioxide is retained and nitrogen and sulfur elements are uniformly introduced into the manganese dioxide lattice, it has the advantages of energy saving and high yield.

[0059] The present invention provides a nitrogen-sulfur dual-doped layered manganese dioxide material prepared by the preparation method described in the above technical solution, including δ-phase layered manganese dioxide and nitrogen and sulfur elements doped in the δ-phase layered manganese dioxide. The nitrogen-sulfur dual-doped layered manganese dioxide material provided by the present invention is mainly a δ-phase layered manganese dioxide material. The present invention dual-dopes manganese dioxide with nitrogen and sulfur elements, and uses the introduced heteroanionic nitrogen and sulfur elements to adjust the electronic structure of the material to improve the intrinsic conductivity of the manganese dioxide material; the bond energy of the Mn-N bond is higher and more stable, which can improve the structural stability of the manganese dioxide material and make the material have a high reversible capacity; the introduction of anionic nitrogen and sulfur elements realizes the formation of partial oxygen vacancies, helps the material expose active sites, and thus improves the overall capacity of the material. In an embodiment of the present invention, the nitrogen-sulfur dual-doped layered manganese dioxide material is expressed as NS-MnO2 material.

[0060] The present invention provides a zinc ion battery, wherein the positive electrode material of the zinc ion battery comprises the nitrogen-sulfur dual-doped layered manganese dioxide material described in the above technical solution.

[0061] In the present invention, the positive electrode material of the zinc ion battery preferably also includes a conductive agent and a binder. The present invention has no special requirements for the conductive agent and the binder, and the conductive agent and the binder well known to those skilled in the art can be used. In an embodiment of the present invention, the conductive agent is preferably conductive carbon black, and the binder is preferably PVDF.

[0062] The present invention preferably mixes the nitrogen-sulfur dual-doped layered manganese dioxide material, a conductive agent and a binder, adds an organic solvent thereto, stirs evenly, and obtains a slurry; the slurry is applied to a current collector, and after drying, the positive electrode of the zinc ion battery is obtained. In the present invention, the mass ratio of the nitrogen-sulfur dual-doped layered manganese dioxide material to the conductive agent and the binder is preferably 7:2:1; the organic solvent is preferably N-methylpyrrolidone (NMP), and the present invention has no special requirements for the amount of the organic solvent, and the amount familiar to those skilled in the art can be used. In the present invention, the current collector is preferably titanium foil, and the loading amount of the nitrogen-sulfur dual-doped layered manganese dioxide material on the current collector is preferably 1.0 to 1.5 mg / cm 2 In the present invention, the drying temperature is preferably 60°C.

[0063] In the present invention, the negative electrode of the zinc ion battery is preferably zinc foil, and the electrolyte of the zinc ion battery preferably includes ZnSO4, MnSO4 and water, that is, the zinc ion battery is preferably an aqueous zinc ion battery. In the present invention, the concentration of ZnSO4 in the electrolyte is preferably 2 mol / L, and the concentration of MnSO4 is preferably 0.1 mol / L.

[0064] The present invention uses the nitrogen-sulfur dual-doped layered manganese dioxide material as a positive electrode material for a zinc ion battery, so that the zinc ion battery has excellent electrochemical performance.

[0065] In order to further illustrate the present invention, the nitrogen-sulfur dual-doped layered manganese dioxide material provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.

[0066] The raw material manganese dioxide (MnO2) used in each embodiment and comparative example is δ-phase layered manganese dioxide, which is prepared by the following method:

[0067] Dissolve 0.6 g potassium permanganate in 100 mL deionized water. After complete dissolution, transfer it to a polytetrafluoroethylene liner, place it in a hydrothermal kettle, and place it in an oven for reaction. The temperature is set to 180°C and the reaction time is 4 hours. After the reaction is completed, wash it with deionized water by centrifugation for 4 times, dry it at 60°C, and set it aside.

[0068] Example 1

[0069] The preparation method of nitrogen-sulfur dual-doped layered manganese dioxide material is as follows:

[0070] 1g of manganese dioxide and 0.2g of thiourea (i.e., the mass ratio of manganese dioxide to thiourea is 1:0.2) are placed at both ends of a double-temperature zone tubular furnace, wherein thiourea is placed on the inlet side and manganese dioxide is placed on the outlet side. The roasting temperature on the outlet side is set to 170°C (heating rate 5°C / min), and the roasting temperature on the inlet side is set to 250°C (heating to the target temperature at the same time as the outlet side), and the holding time is 30min. At 250°C and argon atmosphere (argon is introduced from the inlet side with a flow rate of 25mL / min), thiourea decomposes into hydrogen sulfide and ammonia, reacts with manganese dioxide on the outlet side, and finally cools to room temperature in an argon atmosphere (natural cooling with the furnace), and obtains nitrogen-sulfur doped layered manganese dioxide material, recorded as NS-MnO2 material, and the obtained material is taken out for the next step of characterization and electrochemical performance testing.

[0071] Comparative Example 1

[0072] The preparation method of manganese dioxide material doped with sulfur alone is as follows:

[0073] 1 g of manganese dioxide and 0.2 g of sulfur powder were placed at the two ends of a double-temperature zone tubular furnace, with the sulfur powder placed on the inlet side and the manganese dioxide placed on the outlet side. Argon gas was introduced into the inlet side (flow rate was 25 mL / min), and the roasting temperature on the outlet side was set to 170°C (heating rate was 5°C / min). The roasting temperature on the inlet side was set to 300°C (heated to the target temperature at the same time as the outlet side), and the insulation time was 30 min. Finally, it was cooled to room temperature in an argon atmosphere, and sulfur-doped manganese dioxide material was obtained on the outlet side, recorded as S-MnO2 material.

[0074] Comparative Example 2

[0075] The preparation method of manganese dioxide material doped with nitrogen alone is as follows:

[0076] 1 g of manganese dioxide and 0.2 g of urea were placed at the two ends of a double-temperature zone tubular furnace, with urea placed on the inlet side and manganese dioxide placed on the outlet side. Argon gas was introduced into the inlet side (flow rate was 25 mL / min), and the roasting temperature on the outlet side was set to 170°C (heating rate was 5°C / min). The roasting temperature on the inlet side was set to 160°C (heated to the target temperature at the same time as the outlet side), and the insulation time was 30 min. Finally, it was cooled to room temperature in an argon atmosphere, and nitrogen-doped manganese dioxide material was obtained on the outlet side, recorded as N-MnO2 material.

[0077] Material Characterization:

[0078] Figure 1 The XRD diagrams are of the raw manganese dioxide (MnO2) before doping and the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1. The XRD diagrams show that the raw manganese dioxide and the NS-MnO2 material have the same peak shape as the typical δ-phase layered manganese dioxide material, and the difference in peak intensity may be related to the doping of nitrogen and sulfur elements.

[0079] Figure 2 and Figure 3 These are the scanning electron microscope and transmission electron microscope images of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 1. It can be seen that the surface morphology of the material is in the shape of a curled sheet.

[0080] Figure 4 and Figure 5 They are respectively the N1s photoelectron spectrum and S2p photoelectron spectrum of manganese dioxide (MnO2) before doping and the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1. The successful doping of nitrogen and sulfur elements can be proved by the fine photoelectron spectrum of N and S elements.

[0081] Figure 6The Raman spectra of manganese dioxide (MnO2) before doping and the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1. The Raman spectrum also proves that the obtained material is a layered manganese dioxide in the δ phase, and its peak intensity is weakened compared with the original manganese dioxide because some oxygen vacancies are introduced into the manganese dioxide material during the doping process.

[0082] Electrochemical performance test:

[0083] Battery assembly: The prepared nitrogen-sulfur dual-doped layered manganese dioxide material was mixed with a conductive agent (superP) and a binder (PVDF) in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added. The resulting slurry was stirred evenly and then coated on a titanium foil. The loading of the nitrogen-sulfur dual-doped layered manganese dioxide material was controlled to be 1.0-1.5 mg / cm 2 After drying in a vacuum oven at 60℃, the cells were sliced ​​and assembled into batteries. The electrolyte used was 2M ZnSO4+0.1M MnSO4, the solvent was water, the negative electrode used zinc foil, and the separator used glass fiber separator. Test conditions: All batteries were tested under the Xinwei battery test system.

[0084] Figure 7 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1, at a current density of 0.2 A / g, the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material exhibits a high capacity of 295 mAh / g, and still maintains 99% of the capacity after 100 cycles. Figure 8 This is the charge and discharge curve of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1. It can be seen that its electrode polarization is small, proving the reversibility of its reaction. Fig. 9 The rate performance of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1 shows excellent rate performance under the rate test. After cycling at current densities of 0.2, 0.4, 0.6, 0.8, 1, and 2 A / g, it can still maintain a cycle capacity of 250 mAh / g at 0.2 A / g. Fig.10 The high current (1A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared in Example 1 shows that in the high current cycle of 1A / g, the capacity of 120mAh / g is still maintained at 90% after 1500 cycles.

[0085] Fig.11 This is the small current (0.2 A / g) cycle performance of the original manganese dioxide (MnO2). It can be seen that the attenuation of the original manganese dioxide is more obvious, and the basic capacity retention rate is about 50% after 100 cycles. Fig.12This is the charge and discharge curve of the original manganese dioxide (MnO2). It can be seen from the charge and discharge curve that the polarization of the original manganese dioxide is more serious. Fig.13 This is the high current (1A / g) cycling performance of the original manganese dioxide (MnO2). It can be seen that the initial cycling capacity of the original manganese dioxide material at high current density is high, but it decays quickly, which may be related to its poor conductivity and slow zinc ion transfer kinetics. Fig.14 This is the rate performance of the original manganese dioxide (MnO2). It can be seen that due to its low electrical conductivity and kinetic limitations, its rate performance is poor and it cannot cycle normally at multiple rates.

[0086] The above series of performance tests prove that compared with the original manganese dioxide, the nitrogen-sulfur dual-doped layered manganese dioxide (NS-MnO2) material prepared by the present invention solves the problems of low first charge efficiency, poor cycle stability and low reversible capacity caused by its phase transition. The NS-MnO2 material prepared by the present invention has better cycle stability, rate performance (0.2, 0.4, 0.6, 0.8, 1, 2A / g) and high current charge and discharge capabilities compared to the original MnO2 material.

[0087] Fig.15 The small current (0.2 A / g) cycle performance of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1 shows that its cycle stability is poor. Fig.16 This is the high current (1A / g) cycle diagram of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1. It can be seen that its capacity decays rapidly, but is relatively stable afterwards. This may be related to the fact that sulfur doping improves the intrinsic conductivity of the material, and its capacity decay is related to the instability of the structure. Fig.17 The rate performance of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1 shows that its rate performance has been improved. Fig.18 This is the CV cycle diagram of the sulfur-doped manganese dioxide (S-MnO2) material prepared in Comparative Example 1. It can be seen that its redox peaks are relatively close, indicating that its reaction reversibility is good.

[0088] Fig.19 The small current (0.2 A / g) cycling performance of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2 shows that its cycling stability is good, but its capacity decreases due to the introduction of nitrogen to reduce the valence state of manganese. Fig. 20 The large current (1A / g) cycling performance of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Example 2 shows that nitrogen doping improves the large current cycling stability of the material, but since it reduces the valence state of manganese, the cycling capacity is relatively low. Fig.21 This is the CV cycle diagram of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2. It can be seen that the reversibility of the reaction during the charge and discharge process is good. Fig. 22 This is the rate performance of the nitrogen-doped manganese dioxide (N-MnO2) material prepared in Comparative Example 2. It can be seen that nitrogen doping improves the rate performance of the material.

[0089] The present invention makes the above comparison on the materials doped with single elements, further proving that the materials doped with nitrogen and sulfur have better performance. At the same time, the coulombic efficiency of the doped materials is high, proving that a highly reversible electrochemical reaction has occurred. The performance of the materials doped with single elements is improved compared with the original manganese dioxide, but the cycle stability and rate performance are poor compared with the nitrogen and sulfur doped materials.

[0090] Example 2

[0091] The calcination temperature on the gas outlet side (ie, the MnO2 temperature zone) in Example 1 was set to 180° C., and the rest was the same as Example 1, to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material.

[0092] The electrochemical properties of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 2 were tested using the same test method as the above electrochemical properties test method. Fig.23 The small current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 2 shows that its capacity is relatively low and its stability is good, which indicates that the successful doping of nitrogen and sulfur stabilizes the structure of the material. However, due to the high temperature, part of the layered structure is destroyed, resulting in a decrease in capacity.

[0093] Comparative Example 3

[0094] The calcination temperature on the gas outlet side (ie, the MnO2 temperature zone) in Example 1 was set to 300° C., and the rest was the same as Example 1, to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material.

[0095] The electrochemical properties of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 3 were tested using the same test method as the above electrochemical properties test method. Fig.24 The small current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 3 shows that the increase in calcination temperature significantly destroys its layered structure, resulting in a rapid decay of its capacity.

[0096] Example 3

[0097] The mass ratio of manganese dioxide to thiourea in Example 1 was adjusted to 1:0.3 (1 g manganese dioxide, 0.3 g thiourea), and the rest was the same as Example 1 to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material.

[0098] The electrochemical properties of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 3 were tested using the same test method as the above electrochemical properties test method. Fig.25 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 3 shows that as the proportion of thiourea increases, the capacity of the material decreases.

[0099] Comparative Example 4

[0100] The mass ratio of manganese dioxide to thiourea in Example 1 was adjusted to 1:0.1 (1 g manganese dioxide, 0.1 g thiourea), and the rest was the same as Example 1 to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material.

[0101] The electrochemical properties of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 4 were tested using the same testing method as the above-mentioned electrochemical properties testing method. Fig.26 The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 4 shows that when the proportion of thiourea is too small, the stability of the material deteriorates.

[0102] Comparative Example 5

[0103] The holding time in Example 1 was adjusted to 2 h, and the rest was the same as Example 1 to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material.

[0104] The electrochemical properties of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 5 were tested using the same test method as the above electrochemical properties test method. Fig. 27 The small current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Comparative Example 5 shows that too long a holding time will also affect its structure and reduce the cycling performance.

[0105] Example 4

[0106] The holding time in Example 1 was adjusted to 10 min, and the rest was the same as Example 1 to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material.

[0107] The electrochemical properties of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 4 were tested using the same testing method as the above electrochemical properties testing method. Fig.28The low current (0.2 A / g) cycling performance of the nitrogen-sulfur dual-doped layered manganese dioxide material prepared in Example 4 shows that the insulation time is too short and the reaction is not sufficient, resulting in poor stability.

[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-sulfur dual-doped layered manganese dioxide material, comprising the following steps: The thiourea is placed in a first temperature zone, and the manganese dioxide is placed in a second temperature zone. The thiourea is decomposed into hydrogen sulfide and ammonia in the first temperature zone. The hydrogen sulfide and ammonia are transported to the second temperature zone under the carrier gas to react with the manganese dioxide to obtain a nitrogen-sulfur dual-doped layered manganese dioxide material; the manganese dioxide is a δ-phase layered manganese dioxide, and the temperature of the second temperature zone is 150-200°C.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the manganese dioxide to thiourea is 1:(0.15-0.3).

3. The preparation method according to claim 2, characterized in that: The mass ratio of the manganese dioxide to thiourea is 1:0.

2.

4. The preparation method according to claim 1, characterized in that: The temperature of the first temperature region is 220-300°C.

5. The preparation method according to claim 1, characterized in that: The temperature of the second temperature region is 170-180°C.

6. The preparation method according to claim 1, characterized in that: The carrier gas is argon, and the flow rate of the carrier gas is 20 to 50 mL / min.

7. The preparation method according to any one of claims 1, 4 to 6, characterized in that: The doping reaction time is 10 to 60 minutes.

8. The nitrogen-sulfur co-doped layered manganese dioxide material prepared by the preparation method according to any one of claims 1 to 7, comprising δ-phase layered manganese dioxide and nitrogen and sulfur elements doped in the δ-phase layered manganese dioxide.

9. A zinc ion battery, characterized in that: The positive electrode material of the zinc ion battery comprises the nitrogen-sulfur dual-doped layered manganese dioxide material according to claim 8.

10. The zinc ion battery according to claim 9, characterized in that: The electrolyte of the zinc ion battery includes ZnSO4, MnSO4 and water.

Citation Information

Cited By

  • Modified layered manganese dioxide positive electrode active material, preparation thereof and application of modified layered manganese dioxide positive electrode active material in aqueous zinc ion battery

    CN120097389A

  • Modified layered manganese dioxide cathode active material, its preparation and application in aqueous zinc-ion batteries

    CN120097389B

  • Phenolic aldehyde substance and manganese dioxide composite type positive electrode active material as well as preparation method and application thereof

    CN121172096A